The examination of body compositions with some blood parameters while wrestling - Temur, H. B. (International Journal of Applied Exercise Physiology, 2020)
In this study, Blood Cells (MCV), Red blood cell (RBC), Hemoglobin (HGB), Triglyceride, High density lipoprotein (HDL), Low density lipoprotein (LDL), levels of heart rate values, height, weight, age, body mass index (BMI) and waist / height ratios were investigated.